Skin Penetration of Fatty Acids from Soap Surfactants in Cleansers Dependent on Foam Bubble Size. Issue 1 (10th May 2013) - Sonoda, Junko; Sakai, Takaya; Inoue, Yousuke; Inomata, Yukio
Abstract: Skin cleansers exhibiting less irritation are required. Although most skin cleansers are applied to the skin in a foam state, the amount of surfactant penetrating into the skin is measured in the solution state. Due to the fact that surfactant penetration causes skin irritation, liquid chromatography/mass spectrometry was used in this study to investigate, from the viewpoint of surfactant penetration, the correlation between foam characteristics and the condition of skin treated with foam. Results demonstrated that as the concentration of surfactant in water drainage from the foam decreased, the composition of surfactants in water drainage shifted to contain smaller amounts of longer‐chain surfactants, whereas the bubble size of the foam became smaller, notwithstanding any change in compounds. When several bubble sizes of foam were added to the skin, it was confirmed that the amount of surfactant penetrating into the skin depends on the levels in the water drainage. The amount of surfactant penetrating into the skin increased with foam bubble size. It was thought that the surfactant at the gas–liquid interface cannot act freely, and thus surfactants in the water drainage tended to penetrate the skin. These results suggest that along with the type of surfactant, both foam morphology and the actual way in which the foam is produced are also important factors that need to be considered when designing milder cleansers.